CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Solve:$$5(2x+y)^2-(2x+y)(x-7y)$$


Solution

$$ 5(2x+y)^{2}-(2x+y)(x-7y)$$
$$ \Rightarrow 5(2x+y)(2x+y)-(2x+y)(x-7y)$$
$$ \Rightarrow5 (4x^{2}+2xy+2xy+y^{2})-(2x^{2}+xy-14xy-7y^{2})$$
$$ \Rightarrow 20x^{2}+10xy+10xy+5y^{2}-2x^{2}+13xy+7y^{2}$$
$$ \Rightarrow 18x^{2}+33xy+12y^{2}$$ Answer

1147045_1189120_ans_3344f12fb00943d381c55b133cbad82b.jpg

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More



footer-image